Enhanced Iron Uptake in Plants by Volatile Emissions of Rahnella aquatilis JZ-GX1 - Kong, Wei-Liang; Wang, Ya-Hui; Wu, Xiao-Qin (Frontiers in Plant Science, 2021)
Iron deficiency in soil has crucially restricted agricultural and forestry production. Volatile organic compounds (VOCs) produced by beneficial microorganisms have been proven to play an important role in inducing abiotic stress tolerance in plants. We investigated the effects of VOCs released by the rhizobacterium Rahnella aquatilis JZ-GX1 on the growth and root parameters of Arabidopsis thaliana under iron deficiency. Genes related to iron uptake and hormone signalling pathways were detected by RT-qPCR. Finally, the VOCs of the JZ-GX1 strain that could promote plant growth under iron deficiency stress were screened. The results showed that the JZ-GX1 strain could induce A. thaliana tolerance to iron deficiency stress by promoting the development of lateral roots and root hairs and increasing the activities of H+ ATPase and Fe3+ reductase. In addition, the AHA2, FRO2 and IRT1 genes of A. thaliana exposed to JZ-GX1-emitted VOCs were upregulated 25-, 1.81-, and 1.35-fold, respectively, and expression of the abscisic acid (ABA) synthesis gene NCED3 was upregulated on both the 3rd and 5th days. 2-undecanone and 3-methyl-1-butanol were found to promote Medicago sativa growth under iron-limited conditions. These results demonstrated that the VOCs of R. aquatilis JZ-GX1 have good potential in promoting iron absorption in plants.